Economic Evaluation Enhances Public Health Decision Making - Rabarison, Kristina M.; Bish, Connie L.; Massoudi, Mehran S.; Giles, Wayne H. (Frontiers in Public Health, 2015)
Contemporary public health professionals must address the health needs of a diverse population with constrained budgets and shrinking funds. Economic evaluation contributes to evidence-based decision making by helping the public health community identify, measure, and compare activities with the necessary impact, scalability, and sustainability to optimize population health. Asking “how do investments in public health strategies influence or offset the need for downstream spending on medical care and /or social services?” is important when making decisions about resource allocation and scaling of interventions.